TEACHING SPEAKING USING VOICE NOTE TO SECOND SEMESTER STUDENTS-2021A OF STKIP PGRI SIDOARJO - Sulistyaningsih; Fatur Lutfi Djap (JournEEL, 2022)
The aims of the study were to describe the implementation of teaching speaking by using Voice Notes; and to describe the student’s perceptions in teaching speaking using Voice Notes for second semester students at STKIP PGRI Sidoarjo. The method used descriptive qualitative. The subjects of this study were the lecturer and the 25 students second semester. The instruments were used Observation Check List, Handphone and Questionnaires. The findings of the implementation of teaching speaking by using Voice Notes for second semester students at STKIP PGRI Sidoarjo were first, Lecturer, distributed text and Voice Note to students thru Voice Note in WhatsApp, then explained to students about text of “A Tour Guide in the Everglades National Park”. Lecturer asked to translate all the text on the home work book, then asked the students to shadow and to follow the native speaker’s voice from Voice Note many times, until comprehended. Lecturer evaluated students’ speaking ability, the results were 32% students who got excellent scores, 52% students who got good scores, one student got average score 8% and students who got poor score 12%. While, the students’ perception results were 78,8% liked the implementation of teaching using Voice Note on the other hand 21,2% didn’t like the implementation of teaching using voice note.